Strategi Bertahan Hidup Musisi Jalanan Angklung Arieska Jogja di Jalan Malioboro, Yogyakarta - Nathaniella, Donita Ezra; Kamajaya, Gede; Aditya, I Gst. Ngr. Agung Krisna; Pramestisari, Nyoman Ayu Sukma (JURNAL ILMIAH SOSIOLOGI: SOROT, 2023)
This research focuses on the community of street musicians Angklung Arieska Jogja in developing survival strategies to survive and exist on Malioboro Street, Yogyakarta City. The purpose of this study is to explain how the survival strategy compiled by  Angklung Arieska Jogja Community with the theoretical study of Constructive Functionalism by Pierre Felix Bourdieu. The Angklung Arieska Jogja Community in maintaining its existence as street musicians on Malioboro Street can be seen from how they develop a strategy to survive based on Bourdieu's theory of Constructive Functionalism with the formula (HabitusxModal)+Area= Action. This study uses a qualitative research method with a descriptive-explanative method, because it is very important to use it in obtaining facts and information in the field and can provide explanations related to research. The results of this study explain that there are four survival strategies for street musicians Angklung Arieska Jogja, namely: 1) Introducing traditional music, especially the angklung musical instrument to the wider community, 2) Having good relations with various parties, 3) Utilizing developing technology, 4) Having stage name and social identity. The four strategies are implemented by the Angklung Arieska Jogja community with their habitus and capital, as well as the areas they use to survive with various objectives such as a means of making a living, attracting tourists, and preserving traditional musical instruments.